FIELD-ORIENTED CONTROL OF DUAL-STAR INDUCTION MACHINE WITH ENERGY QUALITY BASED ON FUZZY LOGIC (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Power segmentation offers a solution to ensure service continuity and improve the quality of electrical energy. Multi-star machines powered by voltage inverters are subjected to non-sequential currents, which disturb the fundamental currents and thus deteriorate the quality of the energy supplied by these machines. In this work, a new field-oriented control (NFOC) based on a new mathematical model of the double-star induction machine (DSIM) is proposed. This new model separates the DSIM into two distinct parts (fundamental and secondary), enabling the elimination of these non-sequential currents using fuzzy logic. This also brings the control of the DSIM closer to that of classical three-phase induction machines, resulting in improved regulation and reduced computation time. The new model, along with its new control, has been validated through simulations in MATLAB/Simulink, yielding very interesting results compared to the classical DSIM field-oriented control (CFOC).
Keywords: Dual star induction machine; Field oriented control; Fuzzy logic; Non-sequential components; Energy quality